Pengaruh Harga, Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Produk Kosmetik (Studi Kasus Pengguna Produk Kosmetik Wardah, Emina, Viva Di Kelurahan Pasarbatang Brebes) - Amaliah Amaliah; Yenny Ernitawati; Dwi Harini (Jurnal Manajemen Riset Inovasi, 2023)
This research is about the influence of price, product quality and brand image on purchasing decisions for cosmetic products. The aim of this research is to determine and analyze the influence of price, product quality and brand image on purchasing decisions for cosmetic products. The urgency of this research is seen from consumers who determine purchasing decisions. The population in this study was Pasarbatang Subdistrict with 100 respondents using the Solvin formula. The technique used in sampling is non-probability sampling with a purposive sampling method. This type of research is quantitative. The data collection method uses questionnaires. The results of the research can be concluded that price wardah partially does not have a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions and brand image has a significant effect on purchasing decisions. For the Emina brand, price has no significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions and brand image has a positive effect on purchasing decisions. Meanwhile, for the Viva brand, price does not have a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions and brand image has an influence on purchasing decisions. Meanwhile, in simultaneous testing the three brands had a significant effect. The suggestion in this research is that Wardah, Emina and Viva companies should always pay attention to product prices before marketing their products.